Saliency Processing and Obesity: A Preliminary Imaging Study of the Stop Signal Task - Hendrick, Olivia M. (2011)
Obesity has been associated with altered cerebral functions including cognitive control. The stop signal task (SST) has been widely used to study cognitive control by producing high conflict stop trials among many low conflict go trials. Contrasting these stop trials with go trials provides a measure of saliency processing and response inhibition. By comparing functional magnetic resonance images of obese (BMI >30) and lean (BMI <22) females performing the SST, we observed differences in regional brain activations despite similar behavioral performance between groups. Specifically, lean females had greater activations in the insula, inferior parietal cortex, cuneus, and supplementary motor area than obese females during stop as compared to go trials. This difference was caused by diminished brain activations in obese females in stop as compared to go trials. Furthermore, the brain activations in these regions inversely correlated to BMI across subjects. These preliminary findings suggest altered neural processes of cognitive control in obesity.